THE METAPHYSICAL POETIC STRAND IN THE TRANSLATION OF PETRE M. ANDREEVSKI (Journal of Contemporary Philology, 2018)
This  paper  delves  into  the  English  translation  of  one  of  the  most  renowned Macedonian  poet  and  novelist –Petre  M.  Andreevski.  It  analyses  the translations of two poems, the anthological Making Love to Deniciaand This Side and Beyond; followed by interpretations of the different semantic nuances between the original and the translation (versification). For this purpose, Dragi Mihajlovski’s method known as ‘map of deviation’ is being used in order to present the deviations on a phonological, lexical, syntactic and semantic level. Each  linguistic  estrangement  is  discussed  in  details  and  new  translation equivalents  are  offered  and  justified.  The  aim  is  to  emphasizethe  creative process   of   translation   and   the   never-ending   struggle   of   the   translator, especially in poetry translation. The paper revolves around the translation of the metaphysical elements in some of Andreevski’s poems. In search of better translation equivalents, a new translation of the poems at hand is encompassed towards the end of the paper. The new translation is an attempt to reach the aesthetic equivalent of the original and to translate the untranslatable in poetry
Keywords: poetry; original; versification; translation